Pengaruh Media Audio Visual Terhadap Keterampilan Gerak Jurus Tunggal Siswa Ekstrakurikuler Pencak Silat Di Smk Negeri 2 Karawang - Nurfazriah, Reni; Mahardhika, Dhika Bayu; S, Rhama Nurwanyah (Peneliti.net, 2023)
The Influence Of Audio Visual Media On Single Movement Skills Of Pencak Silat Extracurricular Students At Smk Negeri 2 Karawang This Study Aims To Determine The Effect And Differences Of Direct And Audio-Visual Media Training (Video Tutorials) On Single-Category Pencak Silat Movement Skills At Smk Negeri 2 Karawang. The Research Method Was An Experimental Research Mastery With A Pretest-Posttest Design. The Population In This Study Are Students Of Smk Negeri 2 Karawang, Totaling 30 People With A Sampling Technique Of 30 Sampling. Data Collection And Research Instruments Namely Pretest And Posttest Single Martial Arts Moves. Data Analysis Used The T Test. The Results Showed That Ha: (1) There Was An Effect Of Audio-Visual Training On The Movement Skills Of Single-Category Martial Arts In Students Of Smk Negeri 2 Karawang. Instruments This Study Used The Single Category Pencak Silat Competition Assessment Form. Data Analysis Techniques Used The Pretest Posttest Design. The Results Of This Study Are The Average Pretest Of 78.10 And Posttest Of 87.33. The Results Of The Analysis Of The Paired Sample T Test With The Data Obtained From This Study Are The Significance Value (2-Tailed) = 0.001 Less Than The Significant Level (Α) = 0.05, Then H0 Is Rejected And H1 Is Accepted. It Can Be Concluded That The Effect Of Audio Visual Media On The Single Kick Movement Skills Of Pencak Silat Can Influence To Improve The Single Move Skills Of Pencak Silat Students Of Smk Negeri 2 Karawang.